SARS-CoV-2 Infection among Serially Tested Emergency Medical Services Workers. (23rd October 2020) - Tarabichi, Yasir; Watts, Brook; Collins, Thomas; Margolius, David; Avery, Ann; Gunzler, Douglas; Perzynski, Adam
Abstract: Background: Emerging research has examined the prevalence of severe acute respiratory syndrome virus 2 (SARS-CoV-2) infections in numerous settings, but a critical gap in knowledge is an understanding of the rate of infection among first responders. Methods: We conducted a prospective serial serologic survey by recruiting public first responders from Cleveland area emergency medical services agencies and fire departments. Volunteers submitted a nasopharyngeal swab for SARS-CoV-2 PCR testing and serum samples to detect the presence of antibodies to SARS-CoV-2 on two visits scheduled approximately 3 weeks apart. Results: 296 respondents completed a first visit and 260 completed the second. While 71% of respondents reported exposure to SARS-CoV-2, only 5.4% (95% CI 3.1-8.6) had positive serologic testing. No subjects had a positive PCR. On the first visit, eight (50%) of the test-positive subjects had no symptoms and only one (6.2%) sought healthcare or missed school or work. None of the subjects that tested negative on the first visit were positive on their second. Conclusions: While our results show a relatively low rate of test positivity for SARS-CoV-2 amongst first responders, most were either asymptomatic or mildly symptomatic. The potential risk of asymptomatic transmission both between first responders and from first responders to vulnerable patients requires more study.